PERKEMBANGAN TARI RENTAK KUDO DI KECAMATAN HAMPARAN RAWANG TAHUN 1990-2020 - Arief Rizki Pratama; Najmi Najmi (Jurusan Sejarah FIS UNP, 2021)
This study examines the Rentak Kudo Dance Art which is a traditional dance art located in Hamparan Rawang District. This dance has grown rapidly since 1990 until now. This study aims to explain the developments that occurred in the art of Rentak Kudo starting from its initial popularity in 1990 until 2021. This study uses the Historical research method with Steps; Heusristics, Source Criticism, Data Interpretation, and Historiography. The results of this study indicate that the art of Rentak Kudo Dance underwent significant changes in terms of meaning, procedures, clothing, timing, and musical instruments used in accompanying the performance of Rentak Kudo. In its development, Rentak Kudo art was popularized by one of the figures called Tuke Ngasiuh, namely Mrs. Ruwaida from Tanjung Village, Hamparan Rawang District, who began to popularize Rentak Kudo in various arts and traditional events since 1990 until, entering the early 2000s with the development of increasingly advanced technology Rentak Kudo began to experience changes in various aspects